The Philosophy of Mountains in the Qur’an and Its Lessons on Stability, Resilience, and Environmental Ethics - Johnderose, Ahmad Qolbi; Qur'any, Ibnu Yaqzan; Utama, Muhammad Hafidz Syaputra; Puspitasari, Niken Sylvia (TAFSE: Journal of Qur'anic Studies, 2024)
The Qur’an presents mountains not only as geological formations but as profound symbols of cosmic balance (mīzān), spiritual resilience, and divine wisdom. This study examines their philosophical significance by integrating classical and modern Qur’anic exegesis (tafsir) with contemporary environmental ethics and scientific perspectives. Employing a qualitative approach with thematic and comparative tafsir analysis, this research explores Qur’anic references to mountains (jabal, rawāsi, ṭūr) through interpretations by Al-Tabari, Ibn Kathir, Al-Razi, and M. Quraish Shihab. Findings indicate that mountains function as both stabilizers of the earth and metaphors for human endurance, patience, and revelation. Their Qur’anic depiction aligns with the concept of mīzān (divine balance), illustrating the interconnectedness between natural order and moral responsibility. Additionally, the study emphasizes human stewardship (khalīfah fil ard’) and ethical responsibility toward nature, drawing links between Islamic teachings and contemporary sustainability discourse. By bridging scriptural interpretation with ecological thought, this study underscores how the Qur’anic philosophy of mountains provides ethical insights into environmental conservation.